2009
DOI: 10.1103/physrevlett.102.077201
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Core Switching by Coherent Excitation with Single In-Plane Magnetic Field Pulses

Abstract: The response of magnetic vortex cores to subnanosecond in-plane magnetic field pulses was studied by time-resolved x-ray microscopy. Vortex core reversal was observed and the switching events were located in space and time. This revealed a mechanism of coherent excitation by the leading and trailing edges of the pulse, lowering the field amplitude required for switching. The mechanism was confirmed by micromagnetic simulations and can be understood in terms of gyration around the vortex equilibrium positions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 15 publications
0
66
1
Order By: Relevance
“…Since the vortex polarity is very stable and well controllable, such structures may be used in the future for information storage and data processing devices. It has been demonstrated that the vortex core polarity can be dynamically reversed by exciting one of the eigenmodes of the vortex structure, i.e., the gyrotropic mode [1][2][3][4] or dipolar spin-wave modes. [5][6][7] For the vortex gyrotropic mode G 0 , the vortex core performs a translational motion with frequencies in the range of 100 MHz to 1 GHz (depending on the disk dimensions and the material of the disk).…”
Section: Introductionmentioning
confidence: 99%
“…Since the vortex polarity is very stable and well controllable, such structures may be used in the future for information storage and data processing devices. It has been demonstrated that the vortex core polarity can be dynamically reversed by exciting one of the eigenmodes of the vortex structure, i.e., the gyrotropic mode [1][2][3][4] or dipolar spin-wave modes. [5][6][7] For the vortex gyrotropic mode G 0 , the vortex core performs a translational motion with frequencies in the range of 100 MHz to 1 GHz (depending on the disk dimensions and the material of the disk).…”
Section: Introductionmentioning
confidence: 99%
“…In a vortex-state magnetic nanodisc [1][2][3] , the static magnetization curls in the plane, except in the core region, where it points out of plane 4,5 , either up or down, leading to two possible stable states of opposite core polarity p. Dynamical reversal of p by large-amplitude motion of the vortex core [6][7][8][9] has recently been demonstrated experimentally [10][11][12][13][14] , raising the prospect of practical applications, in particular in magnetic-storage devices…”
mentioning
confidence: 99%
“…Still, selective core-polarity reversal is possible using a circularly polarized microwave magnetic field because the sense of the core rotation is linked by a right-hand rule to its polarity 12 . Control of polarity switching can also be achieved by precise timing of non-resonant magnetic-field pulses 13,19 , in a similar fashion as domain-wall propagation in magnetic nanowires 20 . Resonant amplification 21 of the vortex gyrotropic motion enables us to reverse the core polarity with minimum excitation power 12,14,15 , as it enables us to concentrate the energy in a narrow frequency band.…”
mentioning
confidence: 99%
“…This threshold will differ from the type of in-plane excitation e.g. pulse [67,68], burst [63], or continuous excitation that is applied to the structure, and at least is still a factor of about 100 lower than the switching threshold with a static perpendicular field.…”
Section: Vortex Core Switchingmentioning
confidence: 92%
“…Scanning Transmission X-ray Microsopy (STXM) [63] techniques that utilize Xray Magnetic Circular Dichroism (XMCD) [95] to obtain the magnetic contrast are emerging as one of the premier probes. The vortex core dynamics induced by a pulsed magnetic field has also recently been detected in STXM [68,91]. We have utilized this technique in our experimental work, the detailed description of which will be presented in following chapters.…”
Section: Imaging Methodsmentioning
confidence: 99%